The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/biolre/ioab007
|View full text |Cite
|
Sign up to set email alerts
|

Tex55 encodes a conserved putative A-kinase anchoring protein dispensable for male fertility in the mouse

Abstract: The conserved putative A-kinase anchoring protein TEX55 is not essential for spermatogenesis and fertility in the mouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The fact that a gene is either testis-specific or highly testis-enriched is no indication that its deletion will impair male fertility. Some laboratories have recently generated several dozen testis-enriched knockout mouse lines and shown that all these genes are individually dispensable in terms of male fertility in mice ( Iwamori et al, 2011 ; Miyata et al, 2016 ; Khan et al, 2018 ; Lu et al, 2019 ; Chotiner et al, 2020 ; He et al, 2020 ; Khan et al, 2020 ; Jamin et al, 2021 ). The same is true for lncRNAs since their abundant expression during spermatogenesis has prompted other laboratories to produce knockout mouse models of testis-specific lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that a gene is either testis-specific or highly testis-enriched is no indication that its deletion will impair male fertility. Some laboratories have recently generated several dozen testis-enriched knockout mouse lines and shown that all these genes are individually dispensable in terms of male fertility in mice ( Iwamori et al, 2011 ; Miyata et al, 2016 ; Khan et al, 2018 ; Lu et al, 2019 ; Chotiner et al, 2020 ; He et al, 2020 ; Khan et al, 2020 ; Jamin et al, 2021 ). The same is true for lncRNAs since their abundant expression during spermatogenesis has prompted other laboratories to produce knockout mouse models of testis-specific lncRNAs.…”
Section: Discussionmentioning
confidence: 99%